An fNIRS Investigation of Discrete and Continuous Cognitive Demands During Dual-Task Walking in Young Adults - Rahman, Tabassum Tahmina; Polskaia, Nadia; St-Amant, Gabrielle; Salzman, Talia; Vallejo, Diana Tobón; Lajoie, Yves; Fraser, Sarah Anne (Frontiers in Human Neuroscience, 2021)
Introduction: Dual-task studies have demonstrated that walking is attention-demanding for younger adults. However, numerous studies have attributed this to task type rather than the amount of required to accomplish the task. This study examined four tasks: two discrete (i.e., short intervals of attention) and two continuous (i.e., sustained attention) to determine whether greater attentional demands result in greater dual-task costs due to an overloaded processing capacity. Methods: Nineteen younger adults (21.5 ± 3.6 years, 13 females) completed simple reaction time (SRT) and go/no-go (GNG) discrete cognitive tasks and n-back (NBK) and double number sequence (DNS) continuous cognitive tasks with or without self-paced walking. Prefrontal cerebral hemodynamics were measured using functional near-infrared spectroscopy (fNIRS) and performance was measured using response time, accuracy, and gait speed. Results: Repeated measures ANOVAs revealed decreased accuracy with increasing cognitive demands (p = 0.001) and increased dual-task accuracy costs (p < 0.001). Response times were faster during the single compared to dual tasks during the SRT (p = 0.005) and NBK (p = 0.004). DNS gait speed was also slower in the dual compared to single task (p < 0.001). Neural findings revealed marginally significant interactions between dual-task walking and walking alone in the DNS (p = 0.06) and dual-task walking compared to the NBK cognitive task alone (p = 0.05). Conclusion: Neural findings suggest a trend towards increased PFC activation during continuous tasks. Cognitive and motor measures revealed worse performance during the discrete compared to continuous tasks. Future studies should consider examining different attentional demands of motor tasks.